Produção, propriedades e aplicações de oligossacarídeos - Giese, Ellen Cristine [UNESP]; Hirosi, Tatiana; Corradi da Silva, Maria de Lourdes [UNESP]; da Silva, Roberto [UNESP]; Barbosa, Aneli de Melo (Universidade Estadual de Londrina (UEL), 2011)
Oligosaccharides participate in the formation of dietary fiber and are mainly used as prebiotic agents. This review presents ways of obtaining these sugars, which can be produced by synthesis (chemical or enzymatic), or through depolymerization of polysaccharides (physical, chemical or enzymatic). Oligosaccharides have also been used commercially as an ingredient in cosmetics, pharmaceuticals, agricultural products and especially in the food industry because of their physical properties. The potential applications of oligosaccharides in several areas such as food, animal feed, pharmaceuticals and cosmetics have contributed to the increase in scientific research on these carbohydrates. The use of oligosaccharides as immuno-modulatory agents and biological response modifiers has been recently described, and their effects as anti-inflammatory and in reducing cholesterol. An overview of the various nutraceutical and biological functions of these carbohydrates in order to benefit human health is also reported.
Production, properties and applications of oligosaccharides
Keywords: Oligosaccharides; Dietary fibers; Human health